(untitled) (International Seven Journal of Health Research, 2024)
Poliomyelitis is an acute contagious viral disease that can affect children and adults, causing sequelae, especially in the most severe cases. There is no specific treatment, but prevention is extremely important. The study was exploratory in nature, through a literature review based on references published in Scielo, Google Scholar and VHL. Using a qualitative, descriptive and exploratory methodology, the aim was to educate the population of the Vila Salete Basic Health Unit (BHU) in the municipality of Fraiburgo, SC, about the importance of polio vaccination, as well as the consequences of the disease, given that vaccination coverage at the BHU and in the municipality is below the parameters set by the Ministry of Health (MoH). The extension activities to achieve this goal included guidance at the aforementioned UBS, involving family members who accompanied the children to appointments, on Wednesdays during October 2022, and reinforcing the information through an information folder at the 1st MED DAY, in Fraiburgo, on November 5, 2022. The conclusion is that the population is unaware of the seriousness of this disease, and several diseases that used to hit the population very aggressively can now be considered eradicated, such as polio if we achieve good vaccination coverage.